Modulation of electrical and thermal transports through lattice distortion in BaTi1–xNbxO3 solid solutions. (1st October 2022) - Zhang, Yuqiao; Cho, Hai Jun; Jiang, Feng; Xia, Chengliang; Chen, Yue; Liu, Weishu; Ohta, Hiromichi
Abstract: The electron and heat transports in solids are through the movement of carrier electrons and quantized lattice vibrations (phonons), which are sensitive to the lattice distortion and ionized impurities, and are essential aspects for the development of novel thermoelectric materials. In this study, we systematically investigated the modulations of electrical and thermal conductivities of BaTi1– x Nb x O3 solid solution (BTNO, 0 ≤ x ≤ 1) epitaxial films. At room temperature, BaTiO3 belongs to tetragonal perovskite and exhibits electron conduction through doubly degenerated Ti 3d-t2g orbitals upon doping, while BaNbO3 belongs to cubic perovskite and exhibits metallic electron conduction through partially filled triply degenerate Nb 4d-t2g orbitals. By controlling the Ti/Nb ratio, we found a dual modulation effect on both the lattice structures and conduction band, which affects the electrical and thermal conductivities. Similar to the SrTi1– x Nb x O3 solid solution (STNO, 0 ≤ x ≤ 1) system, a phase transition was detected at x ∼ 0.5, at which both the electron and heat transports exhibit abrupt changes. Unlike the transition in STNO, which was attributed to a polaronic phase transition, the transition in BTNO was due to contributions from both the lattice distortion and polaron effect. By controlling the lattice distortion, conduction band, and polaronic phase transitions, the electrical and thermal conductivity of BTNO epitaxial films are modulated within a much greater range than those of the STNO epitaxial films. Due to the double contribution of electron carriers and phonon to thermal conductivity ( κ ), the maximum κ modulation ratio of BTNO epitaxial films was ∼6.9. Our research provides an effective route to design electrical/thermal management materials.